POTENSI TUMBUHAN JAMBLANG (Syzygium cumini (L.) Skeels) SEBAGAI HEPATOPROTEKTOR BERDASARKAN KANDUNGAN SENYAWA AKTIF : LITERATURE REVIEW ARTICLE - Himyatul Hidayah; Neni Sri Gunarti; Salsa Putri Oktaviani; Surya Amal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Damage to the liver can cause disruption of metabolism in the body, so a hepatoprotector is needed as a protector from liver damage which can be obtained from jamblang plants. The aim of this research is to know the content of active compounds contained in jamblang plants which work as hepatoprotectors. By reviewing some of the literature related to this, the results obtained were 10 articles used. In this study using Literature Review Article through electronic data sources, namely: Google Scholar, ScienceDirect and Pubmed which were published 10 years ago with the keywords: Syzygium cumini (L) and hepatoprotector. Based on the results of the research that has been done, the jamun plant contains the compounds β-sitosterol, friedelin, Betulinic acid, flavonoids, terpenes, alkaloids, phenolics, ellagic acid, glucoside, anthocyanins, kaempferol, quercetin, isoquercetin, myricetin, tannins, carbohydrates, albumin, and so on which can be used as antiviral, cardioprotective, anti-inflammatory, anticancer, antidiabetic, carminative, antihypertensive, anti-atherosclerotic, antifungal, antioxidant and hepatoprotector. It can be concluded that the active compounds that work as hepatoprotectors are the chemical compounds flavonoids and β-sitosterol which are located in the fruit seeds and leaves.